2019
DOI: 10.1371/journal.ppat.1007773
|View full text |Cite
|
Sign up to set email alerts
|

Triggering NETosis via protease-activated receptor (PAR)-2 signaling as a mechanism of hijacking neutrophils function for pathogen benefits

Abstract: Neutrophil-derived networks of DNA-composed extracellular fibers covered with antimicrobial molecules, referred to as neutrophil extracellular traps (NETs), are recognized as a physiological microbicidal mechanism of innate immunity. The formation of NETs is also classified as a model of a cell death called NETosis. Despite intensive research on the NETs formation in response to pathogens, the role of specific bacteria-derived virulence factors in this process, although postulated, is still poorly understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 79 publications
1
59
0
Order By: Relevance
“…As P. gingivalis is one of the most important periodontal pathogens, the DNase expression of six different strains was analyzed, showing all of them had different degrees of DNase activity [54]. P. gingivalis is a potent inducer of NET formation that is mediated by gingipains, but its proteolytical activity has shown to inactivate the bactericidal components of NETs through the activation of protease-activated receptor-2 [55]. Several mutant and wild-type strains of P. gingivalis have been analyzed and their results showed that mutant strains induced a characteristic NET formation [56].…”
Section: Microorganisms' Strategies To Escape the Action Of Netsmentioning
confidence: 99%
See 2 more Smart Citations
“…As P. gingivalis is one of the most important periodontal pathogens, the DNase expression of six different strains was analyzed, showing all of them had different degrees of DNase activity [54]. P. gingivalis is a potent inducer of NET formation that is mediated by gingipains, but its proteolytical activity has shown to inactivate the bactericidal components of NETs through the activation of protease-activated receptor-2 [55]. Several mutant and wild-type strains of P. gingivalis have been analyzed and their results showed that mutant strains induced a characteristic NET formation [56].…”
Section: Microorganisms' Strategies To Escape the Action Of Netsmentioning
confidence: 99%
“…P. gingivalis is found in the oral cavity, where it is implicated in periodontal disease. Furthermore, a novel role has also been demonstrated for proteases as bacterial virulence factors antagonizing the antibacterial activity of NETs [55]. Additionally, the suggested generation of NETs in the periodontium leads to increased inflammation and can be considered another virulence strategy used by P. gingivalis.…”
Section: Microbial Agents Alter Net Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, neutrophils ( Figure 3 ) were isolated as described before from granulocyte-enriched fractions, applied to centrifugation over a density gradient using a lymphocyte separation medium [ 30 ]. Neutrophils and erythrocytes were harvested as the high-density fraction and separated after 30 min of incubation with 1% polyvinyl alcohol (POCH, Warsaw, Poland).…”
Section: Methodsmentioning
confidence: 99%
“…In relation to Figure 3 , Human blood for PMN isolation was purchased from Red Cross, Krakow, Poland as described before [ 30 ]. The Red Cross de-identified blood materials as appropriate for the confidentiality assurance of human subjects.…”
Section: Methodsmentioning
confidence: 99%